2002
DOI: 10.1016/s1470-0328(02)01169-2
|View full text |Cite
|
Sign up to set email alerts
|

Haemodynamic changes in the brain after vaginal delivery and caesarean section in healthy term infants

Abstract: Objective To investigate whether the mode of delivery may affect neonatal cerebral haemodynamics during the first hour of life. Design Prospective study.Sample Healthy infants with gestational age ! 37 weeks and birthweight appropriate for gestational age, born after uncomplicated pregnancy by vaginal delivery or elective caesarean section, two to five hours after the delivery. Methods Near infra-red spectroscopy was used to measure changes of oxygenated haemoglobin, deoxygenated haemoglobin, oxidized-reduced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2004
2004
2004
2004

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 18 publications
(22 reference statements)
0
2
0
Order By: Relevance
“…Hypoxemia is also a strong vasodilator, while an increase in oxygen tension correlates with decreased cerebral blood flow velocities20, 21. However, in a more recent study it was reported that arterial oxygen saturation and carbon dioxide tension did not change significantly in newborns16. The increase in cerebral blood flow velocity at 24 h after birth depends on multiple factors and is not completely clear; the increase in arterial blood pressure, ductal closure and increase in cerebral metabolism probably play an important role11.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Hypoxemia is also a strong vasodilator, while an increase in oxygen tension correlates with decreased cerebral blood flow velocities20, 21. However, in a more recent study it was reported that arterial oxygen saturation and carbon dioxide tension did not change significantly in newborns16. The increase in cerebral blood flow velocity at 24 h after birth depends on multiple factors and is not completely clear; the increase in arterial blood pressure, ductal closure and increase in cerebral metabolism probably play an important role11.…”
Section: Discussionmentioning
confidence: 94%
“…Indeed, the blood flow available to the infant for organ perfusion in early neonatal life is equal to left ventricular output, minus the volume of left‐to‐right ductal shunting15. The left‐to‐right shunt through the ductus arteriosus, which progressively increases in the first hours of life contemporaneously with the physiological drop in pulmonary vascular resistance, could favor the progressive lowering of cerebral perfusion16. In fact, it has been shown that in cases of patent ductus arteriosus, cerebral diastolic blood flow velocities decrease and the resistance index increases in newborn infants17.…”
Section: Discussionmentioning
confidence: 99%